MyIsyARat: Bridging Communication Gaps through Bahasa Isyarat Malaysia (BIM) with Augmented Reality (AR) - Harizan, Hanief Haiqal; Rosdee, Muhammad Bazil Akid; Alimun, Muhammad Irfan; Mohd Hanifa, Rafizah (Multidisciplinary Applied Research and Innovation, 2026)
Bahasa Isyarat Malaysia (BIM) is the primary visual language of the Malaysian Deaf community, yet it remains underrepresented in mainstream education and digital platforms. To address this gap, MyIsyARat was developed, i.e., an augmented reality (AR)-based mobile application designed to support interactive and engaging BIM learning. Using the Multimedia Development Life Cycle (MDLC) model, the app features 3D animated signs across three key themes: Kata Ganti Nama (Pronouns), Ucapan (Greetings), and Keluarga (Family). User testing involving diverse participants showed strong positive feedback, with average mean scores of 4.57 for App Usability, 4.66 for Content Quality, and 4.65 for Engagement and Learning Experience. These results indicate high levels of user satisfaction and acceptance. More than just a learning tool, MyIsyARat fosters inclusivity, promotes empathy, and supports communication between Deaf and hearing communities, moving one step closer to language equity in Malaysia.